Cost-Utility Analysis of a Six-Weeks Ganoderma Lucidum-Based Treatment for Women with Fibromyalgia: A Randomized Double-Blind, Active Placebo-Controlled Trial. Issue 3 (2nd October 2015) - Garcia-Gordillo, Miguel A.; Collado-Mateo, Daniel; Hernández-Mocholi, Miguel A.; Pazzi, Francesco; Gusi, Narcis; Dominguez-Muñoz, Francisco J.; Adsuar, Jose C.
Abstract: Purpose: To determine the effectiveness of adding Ganoderma lucidum (GL) to standard care for patients with fibromyalgia (FM), and to examine the costs per quality-adjusted life year (QALY) gained from this nutritional supplementation. Materials and methods: This was a randomised controlled trial with a random allocation of participants to two groups; experimental group and active-placebo controlled group. A total of 26 women with FM participated in the experimental group. These participants were instructed to take 3 g of micromilled GL twice a day for six weeks. EQ-5D-5L was used to obtain the utilities and a non-parametric bootstrap was used to plot the acceptability curve. Results: Of the women initially recruited, over 81% completed the experimental treatment. The incremental QALY in the GL group was 0.177, and the incremental QALY in the active placebo group was 0.101. Therefore, the difference in terms of QALYs was 0.076 and the incremental cost-utility ratio was €1348.55/QALYs. The cost-utility acceptability curve showed 90% probability that the addition of GL to the standard care as a nutritional supplement is cost-effective. Conclusions: The GL as nutritional supplementation in patients with FM is cost-effective in women with FM. To authors' knowledge, the current study reports the first cost-utility analysis of GL as a nutritional supplement.